The Role of Supervisor in Improving Service Quality at Lumbini Restaurant, Ubud Nyuh Bali Resort and Spa - Wirawan, Dewa Nyoman Deni; Sulastri, Ida Ayu Putu; Wiantara, I Gusti Nyoman (LPPM Universitas Dhyana Pura, 2026)
Service quality in hotel restaurant operations is closely linked to the effectiveness of supervisor leadership and supervision. This study aims to analyze the role of the supervisor in improving service quality at Lumbini Restaurant, Ubud Nyuh Bali Resort and Spa; identify the challenges encountered; and describe the efforts made to overcome them. A qualitative descriptive approach was employed, with data collected through direct observation, in-depth interviews with the Restaurant Supervisor, and documentation during the research period. The results show that the supervisor plays five critical roles: supervising restaurant operations, directing and controlling staff performance, ensuring SOP compliance, providing coaching and motivation, and conducting service evaluations. Challenges identified include insufficient staff discipline, lack of product knowledge mastery, inaccurate order-taking, insufficient attention to guest needs, and poor inter-staff coordination and communication. To address these challenges, the supervisor implements daily and monthly briefings, monthly SOP training, product knowledge training, taking order training, direct operational supervision, and continuous staff feedback. This study concludes that the supervisor's active and consistent role in supervision, coaching, and evaluation is essential to improving service quality and staff competence, and ultimately to achieving guest satisfaction at Lumbini Restaurant.